2023
DOI: 10.17358/ijbe.9.1.36
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Manager Behavior in Explaining The Financial Planning And Financial Innovation of Small and Medium Enterprises

Abstract: The major weakness of SMEs is in financial management and marketing. These problems obstruct their growth and ability to plan and innovate their business. This study examines the influence of personality, financial culture, and competence on SMEs' innovation and financial planning. The sample was determined by proportional random sampling repose industry type, and 285 complete data were analyzed. Data were collected through a structured offline questionnaire. A quantitative analysis approach was followed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…However, it was also revealed that most of these people retained the habit of saving resources in everyday life [44]. The habit of controlling cash flows both in private life and in business management correlates well with the habit of controlling the consumption of resources such as water, electricity, and heat consumption [45]. One of the reasons why habits are fundamentally difficult to "undo" is that they are controlled by other neural networks compared to intent-based behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also revealed that most of these people retained the habit of saving resources in everyday life [44]. The habit of controlling cash flows both in private life and in business management correlates well with the habit of controlling the consumption of resources such as water, electricity, and heat consumption [45]. One of the reasons why habits are fundamentally difficult to "undo" is that they are controlled by other neural networks compared to intent-based behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Secara sederhana, pengambilan keputusan untuk melihat tingkat normalitas residual atau data caranya adalah dengan melihat hasil dari nilai probablitity dan dibandingkan dengan tingkat alpha sebesar 0,05. Jika nilai probability lebih besar dari 0,05 maka dapat diputuskan bahwa data terdistribusi normal (Ismanto & Pebruary, 2021). Jika dilihat pada data Tabel 7 di atas, dapat diinterpretasikan bahwa terdapat pengaruh signifikan yang negatif antara harga minyak dunia pada nilai tukar.…”
Section: Uji Asumsi Klasik Uji Normalitasunclassified
“…Uji koefisien determinasi diterapkan untuk mengetahui tingkat besaran proporsi dari variabel dependen yang dapat dijelaskan oleh variabel independennya dalam suatu model regresi. Semakin tinggi nilai dari koefisien determinasi (nilai R-Squared) dalam suatu model regresi atau mendekati angka 1 maka semakin baik variabel independen dalam menjelaskan variabel dependennya begitu juga sebaliknya (Ismanto & Pebruary, 2021).…”
Section: Uji Koefisien Determinasiunclassified